The Craft Of Modal Counterpoint. - Benjamin, Thomas (Routledge, 2005)
The companion book to Benjamin's recently republished Craft of Tonal Counterpoint, this entirely rewritten second edition provides a complete analysis of modal counterpoint - the important musical style that forms the basis of all early music.